Ion-plus salinity gradient flow Battery. (18th May 2022) - Jiang, Chenxiao; Mei, Ying; Chen, Binglun; Li, Xianhui; Yang, Zhe; Guo, Hao; Shao, Senlin; Tan, Siew-Chong; Xu, Tongwen; Tang, Chuyang Y.
Graphical abstract: Highlights: An Ion-plus salinity gradient flow battery (SGFB) was firstly proposed. Ion-plus system efficiently increased transformation of salinity gradient energy. H +, Li +, Na +, K +, Mg 2+ -plus systems were elected for evaluation. Ion-plus SGFB provide an alternative for green chemical engineering processes. Abstract: A Salinity Gradient Flow Battery (SGFB), as a novel energy-converting system, offered an alternative solution for the large-scale storage of renewable energy. Nevertheless, the commercialization of SGFB had been halted because the relatively high ohmic solution resistance in the low salinity solution. We proposed an "Ion-plus SGFB" system by internally-integrating the redox flow battery and SGFB system for the breakthrough of energy transforming efficiency in SGFB. The supporting ions in the salinity solutions overcome the trade-off limitation between Donnan potential and electrical-resistance as well as accelerate the ion transfer (mass transfer) without sacrificing on the SGP. The results suggest that 62.42–90.68% electric resistance was reduced, and the power density was more than doubled in the nonoptimized system. The novel designed system is environmental-friendly and gentle for membranes, and provided an effective option for the treatment of wastewater and the recovery of useful salinity gradient energy.